O governo Lula e a mídia impressa: estudo sobre a construção de um pensamento hegemônico - Carvalho, Rodrigo (2016)
Brazil is going through a rich process of political debate and struggle in wich the ideas and ideologies are in an outspoken process of formulations and reformulations. The experience of Lula government improve the formulation about ideologies and governments within the scene of political and intelectual combat into the society. The contemporary democracy ensure the interchange, not just of political parties, political forces or historical personality, but above all the building and rebuilding of thinking and action line of the State and the society. The newspapers have a historical role in the status struggle and disputes for hegemonic positions traditionally aligned with liberalism. By means of this particular historical moment and those politicals and socials agents (government types and news coverage) can be identify the construction and the behavior of the hegemonic liberal thought in Brazil. This thesis aim to realize the ideological review of newspapers and the contradictions that there is in those channels. This thesis search also to contribute to identify the particulars of Lula age. Through the editorials of the newspapers Folha de S. Paulo and O Estado de S. Paulo it were realized quantitatives researches for method of valência and qualitative for interpretative research and bibliographic studies. The concept of Hegemony treated in this thesis is based on formulation of the Itlyan philosopher Antônio Gramsci